Impact of prior coronary artery bypass grafting in patients undergoing chronic total occlusion‐percutaneous coronary intervention: Procedural and clinical outcomes from the REgistry of Crossboss and Hybrid procedures in FrAnce, the NetheRlands, BelGium, and UnitEd Kingdom (RECHARGE). Issue 1 (5th May 2020) - Budassi, Simone; Zivelonghi, Carlo; Dens, Joseph; Bagnall, Alan J.; Knaapen, Paul; Avran, Alexandre; Spratt, James C.; Walsh, Simon; Faurie, Benjamin; Agostoni, Pierfrancesco; ,
Abstract: Aim: Chronic total occlusions (CTO) in patients with history of coronary artery bypass graft (CABG) show more advanced and complex atherosclerotic pathology. Aim of our study is to compare outcomes in patients undergoing CTO percutaneous coronary intervention (PCI) with previous CABG versus those without in the REgistry of Crossboss and Hybrid procedures in FrAnce the NetheRlands, BelGium and UnitEd Kingdom (RECHARGE). Methods & results: The RECHARGE cohort (1, 252 patients) was divided in two groups according to the presence of previous CABG (217) or not. We also focused, in the post‐CABG group, on a comparison between CTO in previously grafted vessels versus non‐grafted vessels. The CTO complexity scores were higher and the success rate (71.9% vs. 88.7%, p < .001) was lower in the CABG group, this difference was driven by higher failure rates in high‐complexity‐score CTO. The rate of in‐hospital complications was similar. In the post‐CABG group, the procedural success of CTO located in previously grafted vessels versus those in vessels not previously grafted, was comparably suboptimal (73.1% vs. 68%, p = .47). Conclusion: Patients undergoing CTO PCI with prior CABG have a higher prevalence of comorbidities and more complex lesion characteristics. In the post‐CABG population the success rate was significantly lower, particularly in high CTO complexity scores, though complication rates were comparable. In the post‐CABG population, the CTO success rate was independent of the presence of a previous graft on the CTO vessel.